2008
DOI: 10.1007/s10995-008-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Ethnic, and Economic Disparities in the Prevalence of Pregnancy Complications

Abstract: Pregnancy complications are common and not adequately measured by hospitalizations alone. Both more research and improved surveillance are needed to understand the effect of pregnancy complications on women's health and the reasons for the increased risk among poor or black women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Previous research has shown that low-income individuals have higher preterm birth (PTB) and low birth weight (LBW) rates [3-7]. In addition, non-Hispanic African Americans compared to Non-Hispanic whites consistently have had at least twice the rate of LBW babies and 1.5 times the rate of PTBs [8], and previous studies controlling for socioeconomic status (SES) factors show racial disparities persist [9-11]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that low-income individuals have higher preterm birth (PTB) and low birth weight (LBW) rates [3-7]. In addition, non-Hispanic African Americans compared to Non-Hispanic whites consistently have had at least twice the rate of LBW babies and 1.5 times the rate of PTBs [8], and previous studies controlling for socioeconomic status (SES) factors show racial disparities persist [9-11]. …”
Section: Introductionmentioning
confidence: 99%
“…Under the Taiwan NHI program all pregnant women are allowed to have 10 free scheduled prenatal care visits and include routine screening and treatment for asymptomatic bacteriuria. Therefore, in the study we found that the UTIs prevalence rates among Taiwanese pregnancy women were much lower (8.6%) than among westerners (24.2–16.6%) (2). Furthermore, the incidence of antepartum pyelonephritis was only 0.34%, which is less than that reported in the 1970s (3–4%) before the universal screening for asymptomatic bacteriuria was used.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore pregnancy is considered a risk factor for UTI. The incidence can be as high as 17% in pregnant women in the United States (2).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have called for the development of a national surveillance system so that complications can be better ascertained, monitored, and studied. 5,[32][33][34][35] However, the lack of clear definitions and consistent methods hinders attempts to conduct national surveillance. A practical alternative may be to establish a system of monitoring selected priority morbidities, and factors associated with them, in defined populations, such as multiple managed care organizations [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%